ANALYSIS OF THE SPECTRAL ENERGY DISTRIBUTION OFTHE COOLEST RCrB TYPE CARBON STAR DY Per - Yakovina, L. A.; Shavrina, A. V.; Pavlenko, Ya. V.; Pugach, A. F. (Одеські астрономічні публікації, 2008)
We analysed the spectral energy distribution of the evolved carbon star DY Per by spectral synthesis technique. The red giant shows the photometric features of R CrB type stars. We derived the atmosphere parameters of DY Per using three variants of molecular line lists. The range of Teff estimations is 2900 < Teff < 3300 K. We adopted log g = 0. The star can be metal deficient and hydrogen deficient. The highest value of carbon abundance [C]=0.94 provides the combination of atmosphere parameters Teeff =3100 K, [Fe/H] =0, log(C/O)=0.6, [N/Fe]=0, (H/He)sun with Jorgensen’s line lists for molecules C2 and CN.